Whole-genome sequencing of a year-round fruiting jackfruit (Artocarpus heterophyllus Lam.) reveals high levels of single nucleotide variation - Islam, Tofazzal; Afroz, Nadia; Koh, ChuShin; Hoque, M. Nazmul; Rahman, Md. Jillur; Gupta, Dipali Rani; Mahmud, Nur Uddin; Nahid, Abdullah Al; Islam, Rashedul; Bhowmik, Pankaj K.; Sharpe, Andrew G. (Frontiers in Plant Science, 2022)
Jackfruit (Artocarpus heterophyllus Lam.) is the national fruit of Bangladesh and produces fruit in the summer season only. However, jackfruit is not commercially grown in Bangladesh because of an extremely high variation in fruit quality, short seasonal fruiting (June-August), and susceptibility to abiotic stresses. Conversely, a year-round jackfruit variety, BARI Kanthal-3 developed by the Bangladesh Agricultural Research Institute (BARI) derived from a wild accession found in Ramgarh of Chattogram Hiltracts of Bangladesh, provides fruits from September to June. This study generated a draft whole genome sequence (WGS) of BARI Kanthal-3 to obtain molecular insights into this important unique variety. The estimated genome size of BARI Kanthal-3 was 1.04 giga base pairs (Gbp) with a heterozygosity rate of 1.62%. De novo assembly yielded a scaffolded 817.7 Mb genome while a reference-guided approach, yielded 843 Mb of genome sequence. The estimated GC content was 34.10%. Variant analysis revealed that BARI Kanthal-3 included 5.7 M (35%) and 10.4 M (65%) simple and heterozygous single nucleotide polymorphisms (SNPs), and about 90% of all these polymorphisms are in intergenic regions. Through BUSCO assessment, 97.2% of the core genes were represented in the assembly with 1.3% and 1.5% either fragmented or missing, respectively. By comparing identified orthologous gene groups in BARI Kanthal-3 with five closely and one distantly related species of, 10,092 common orthogroups were found across the genomes of the six species. The phylogenetic analysis of the shared orthogroups showed that A. heterophyllus was the closest species to BARI Kanthal-3 and orthogroups related to flowering time were found to be more highly prevalent in BARI-Kanthal compared to the other Arctocarpus spp. The findings of this study will help better understand the evolution, domestication, phylogenetic relationships, year-round fruiting of this highly nutritious fruit crop as well as provide a resource for molecular breeding.